2018
DOI: 10.3389/fendo.2018.00710
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Orexin-A Levels Do Not Undergo Circadian Rhythm in Young Healthy Male Subjects

Abstract: Orexin-A (OXA) has been originally isolated from a precursor peptide prepro-orexin from the lateral hypothalamus. The orexin system has been attributed to important functions in sleep, arousal and regulation of energy homeostasis. In addition to its high levels in cerebrospinal fluid, OXA is present in blood. However, reported peptide concentrations in plasma vary significantly depending on the method used. Therefore, a specific and sensitive OXA radioimmunoassay (RIA) with solid phase extraction method was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 44 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…A recent publication from the group using this assay reported daytime levels in the range of 2 pg/mL. 44 The antibody has not been widely distributed or commercialised to my knowledge.…”
Section: Second-generation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent publication from the group using this assay reported daytime levels in the range of 2 pg/mL. 44 The antibody has not been widely distributed or commercialised to my knowledge.…”
Section: Second-generation Assaysmentioning
confidence: 99%
“…With chloroform extraction from a neutral buffer, the authors measured daytime melatonin levels in the order of 4.6 pg/mL. A recent publication from the group using this assay reported daytime levels in the range of 2 pg/mL . The antibody has not been widely distributed or commercialised to my knowledge.…”
Section: Melatonin Measurementmentioning
confidence: 99%
“…In healthy humans, orexin can be detected (range 250-500 pg/ml) in cerebrospinal fluid (CSF), but it is generally not detected (<40 pg/ml) in blood by a standard orexin radioimmunoassay, which is used for the diagnosis of narcolepsy, because it cannot cross the BBB. By using a novel specific and sensitive orexin radioimmunoassay, blood orexin can be detected at very low levels (range 0.5-16 pg/ml), but it does not correlate with the wake/sleep cycle (Makela et al, 2018). Surprisingly, we previously reported that orexin improved survival in mice with endotoxin shock, a well-studied animal model of sepsis, by acting in the brain (Ogawa et al, 2016), indicating that orexin may be involved in the pathophysiology of SAE and be a new agent in targeting the CNS for the treatment of sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Messina and colleagues [ 121 ] reported that PA using a calibrated mechanically braked cycle ergometer (at 75 W for 15 min) increased orexin-A levels in plasma of humans from 2610 ± 187 pg/mL to a maximum level (3589 ± 197 pg/mL) within 30 min after exercise. While relative changes in orexin blood levels may be due to experimental differences, absolute levels are still unclear as commercial kits and extraction protocols differ significantly compared to an in-house generated antibody with plasma levels in the range of 1–16 pg/mL [ 122 ].…”
Section: Orexinsmentioning
confidence: 99%